The moral relationship - Gibb, M (2012)
This thesis aims to articulate and defend a version of a 'relational moral theory.' Many philosophers have argued that the non-instrumental value of certain relationships, such as friendship and parenthood, can explain at least some of our moral obligations. A relational moral theory extends this thought by arguing that all, or most, of our moral judgements can be explained by the non-instrumental value of one or more interpersonal relationships. The plausibility of such views depend on the possibility of identifying a relationship that all moral agents share a 'moral relationship'. While the idea of such a relationship has featured in ethical writings as early as the Stoics, few attempts have been made to develop a rigorous and precise understanding of this relationship. This thesis therefore aims to articulate and defend a plausible understanding of the moral relationship, and then to use it as a basis for outlining the structure of a genuinely relational moral theory. It will argue that the moral relationship is best understood as a broad and inclusive relationship shared by all who are vulnerable to a distinct kind of 'second-order evil.' It will then argue that the value of this relationship can provide the basis for a relational form of a contractualist moral theory based on the work of T.M. Scanlon. Understanding the nature of the moral relationship, and the role it plays in such theories, will then be seen as a means of unifying, clarifying, and responding to a number of influential objections against such theories, including objections concerning its capacity to accommodate intuitions concerning cases of aggregation and our obligations to future persons.